Implementation of E-Administration for Public Accountability of Simultaneous PILKADES 2025 in Cianjur - Mulyadi, Dedi; Suheri, Agus; Nurpandi, Finsa; Utami, Tanti Kirana; Mulyana, Aji; Susilawati, Eli; Nurmariam, Yuli (Universitas Negeri Gorontalo, 2025)
The Village Head Election (PILKADES) is a crucial process in Indonesia's democracy, where the village head plays a central role in governance and community service. To enhance the quality of the upcoming simultaneous Pilkades in Cianjur Regency in 2025-2026, the E-Administration system is being implemented. This system aims to streamline the registration of village head candidates, improving accountability, transparency, and efficiency, while reducing the potential for data manipulation. The research aims to evaluate the E-Administration system’s implementation and assess its impact on transparency, efficiency, and accountability in the Pilkades process. Additionally, it seeks to provide a model that other regions can adopt in their Pilkades. The research method includes several strategic stages: a Focus Group Discussion (FGD) to align stakeholder understanding, mentoring in the implementation of the system, and continuous evaluation. The results show a significant improvement in the efficiency of candidate registration, with faster verification and fewer data errors. The system has also increased transparency and accountability, with real-time access to data for authorities and the public. The reduction in data manipulation, through digital verification of documents, highlights the potential for the E-Administration system to be a model for other regions to enhance Pilkades quality.